PENERAPAN HUKUM DALAM PENYELESAIAN KASUS PIDANA TERHADAP OKNUM PANDITA (KAJIAN PUTUSAN NO 266/Pid.B/2021/PN Dps) - NI LUH ARININGSIH SARI (Universitas Mahasaraswati K. Mataram, 2022)
The purpose of this study is to find out how the law is applied to an individual Pandita who is a holy person (purified) according to Hinduism when he is exposed to a criminal case (immoral crime), and to find out what the judges consider in giving their decision as stated contained in Decision Number 266/ Pid.B/2021/PN Dps. In this study used 3 (three) approaches, namely: a. the statutory approach, b. Conceptual approach, c. Philosophical approach. In the application of law to an individual who is involved in a criminal case, there are two legal systems, namely the application of customary law, namely: with the revocation of the defendant's kesulinggihan status so that he returns to being a walaka (a person outside of the sulinggih) so that there is no word